2019
DOI: 10.3171/2019.3.focus1970
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery versus stereotactic radiotherapy in the management of intracranial meningiomas: a systematic review and meta-analysis

Abstract: OBJECTIVEStereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT) have been used as a primary treatment or adjuvant to resection in the management of intracranial meningiomas (ICMs). The aim of this analysis is to compare the safety and long-term efficacy of SRS and SRT in patients with primary or recurrent ICMs.METHODSA systematic review of the literature comparing SRT and SRS in the same study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to suggest an optimal cut-off value for meningioma volume that predicts PTBE in patients with convexity and parasagittal meningiomas. Determining whether to treat small or large meningiomas with stereotactic radiosurgery or fractionated stereotactic radiotherapy or surgery based on a meningioma diameter of 3 cm without any specific reference studies or data has been accomplished by implicit consent among clinicians [ 9 13 ]. Therefore, we believe that our findings may be valuable because we have shown why a meningioma 3 cm diameter can be established as a clinically meaningful standard for the treatment of convexity and parasagittal meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to suggest an optimal cut-off value for meningioma volume that predicts PTBE in patients with convexity and parasagittal meningiomas. Determining whether to treat small or large meningiomas with stereotactic radiosurgery or fractionated stereotactic radiotherapy or surgery based on a meningioma diameter of 3 cm without any specific reference studies or data has been accomplished by implicit consent among clinicians [ 9 13 ]. Therefore, we believe that our findings may be valuable because we have shown why a meningioma 3 cm diameter can be established as a clinically meaningful standard for the treatment of convexity and parasagittal meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we wanted to evaluate the pure association between meningioma size and PTBE occurrence without surgery or radiation therapy in patients with meningiomas at similar locations. In addition, based on clinical experience or implicit consent, most physicians decided on whether to perform surgery or initiate radiation treatment based on a meningioma diameter of 3 cm, without any scientific reference [ 9 13 ]. Therefore, to verify the validity of this size as a clinically meaningful standard for treatment, we needed to evaluate the cut-off value for meningioma size that predicts PTBE development in patients with meningiomas.…”
Section: Introductionmentioning
confidence: 99%
“…Manabe et al using LINAC-based FSRT (25 Gy in 2–10 fractions) in 14 patients with tumor volume > 13.5 cm 3 reported that the 3-year progression-free survival rate was 69% 21 . In a systemic review, despite the potential systemic error in the measurement, Fatima et al proposed that the larger tumors treated with FSRT (5–10 fractions) are significantly associated with better LCR and with higher extent of tumor shrinkage compared with the smaller tumors treated with SRS (< 5 fractions; p = 0.007 and p = 0.72, respectively) 22 . Han et al compared the effectiveness of SSRS (n = 42) and FSRT (n = 28) in the treatment of large meningiomas (> 10 cm 3 ); there were 16 skull base meningioma in FSRT group.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of neurosurgical diseases have been revolutionized due to greater stride observed in terms of systematic therapy, radiotherapy, and surgical techniques 1-3 , 4,5,6,78,9 . The multimodal management has resulted in achieving better clinical and functional outcomes 13,14 .…”
Section: Introductionmentioning
confidence: 99%